Geography: the human and physical world - Boehm, Richard G. (McGraw-Hill networks, 2018)
Unit 1. The World -- Unit 2. The United States and Canada -- Unit 3. Latin America -- Unit 4. Europe -- Unit 5. North Africa, Southwest Asia, and Central Asia -- Unit 6. Africa South of the Sahara -- Unit 7. South Asia -- Unit 8. East Asia -- Unit 9. Southeast Asia and the Pacific World